Total postoperative analgesia for total knee arthroplasty: ultrasound guided single injection modified 4 in 1 block - Ritesh Roy; Gaurav Agarwal; Chandrasekhar Pradhan; Debasis Kuanar (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Total pain free outcome following total knee arthroplasty has led to the evolution of regional blocks. In this series, the authors have revisited and modified Roy et al. 's technique of Ultrasound guided 4 in 1 block for knee and below knee surgeries, to provide a complete comprehensive yet simple single injection technique for postoperative analgesia for Total Knee Arthroplasty (TKA). Material and Methods: After Instituional ethics approval, we performed the modified 4 in 1 block on 10 consenting patients scheduled to undergo total knee arthroplasty. A linear USG-probe was used to identify medial femoral condyle, then vastus and sartorius intersection was identified. The probe was slid till the descending genicular artery branching from superficial femoral artery was visualized proximal to hiatus. At this point the needle with PNS attached, was guided into the Vastus medialis muscle till the stimulation of the nerve to Vastus medialis (0.4-0.5 mA). At this point 5-7 mL of 0.2% Ropivacaine was injected. The needle was guided in plane to perivascular region and after negative aspiration 0.2%ropivacaine 20-25 ml was injected, visualised to push the femoral artery. Results: All ten patients considered in this study had an optimum pain score of <5 and were comfortable along with no quadriceps weakness, except one patient had a pain score of more than 5 after 36 hr post-operatively and required rescue analgesia. Conclusion: The addition of USG and PNS guided Vastus medialis nerve block to USG 4-in-1 block in the technique gives good post-operative analgesia for TKA.